An Extremely Compact, Low-mass Galaxy on its Way to Quiescence at z = 5.2 - Strait, Victoria; Brammer, Gabriel; Muzzin, Adam; Desprez, Guillaume; Asada, Yoshihisa; Abraham, Roberto; Bradač, Maruša; Iyer, Kartheik G.; Martis, Nicholas; Mowla, Lamiya; Noirot, Gaël; Sarrouh, Ghassan T. E.; et al. (Astrophysical journal. Letters, 2023)
We report the discovery of a low-mass z = 5.200 ± 0.002 galaxy that is in the process of ceasing its star formation. The galaxy, MACS0417-z5BBG, is multiply imaged with magnification factors ∼40 by the galaxy cluster MACS J0417.5-1154, observed as part of the CAnadian NIRISS Unbiased Cluster Survey (CANUCS). Using observations of MACS0417-z5BBG with a JWST/NIRSpec Prism spectrum and NIRCam imaging, we investigate the mechanism responsible for the cessation of star formation of the galaxy and speculate about possibilities for its future. Using spectrophotometric fitting, we find a remarkably low stellar mass of M * = 4.3 ± 0.8 0.9 × 10 7 M ⊙ , less than 1% of the characteristic stellar mass at z ∼ 5. We measure a delensed rest-UV half-light radius in the source plane of 30 ± 5 7 pc and measure a star formation rate from H α of 0.14 ± 0.12 0.17 M ⊙ yr −1 . We find that under the assumption of a double power-law star formation history, MACS0417-z5BBG has seen a recent rise in star formation, peaking ∼10–30 Myr ago and declining precipitously since then. Together, these measurements reveal a low-mass, extremely compact galaxy which is in the process of ceasing star formation. We investigate the possibilities of mechanisms that have led to the cessation of star formation in MACS0417-z5BBG, considering stellar and active galactic nuclei (AGN) feedback and environmental processes. We can likely rule out most environmental processes but leave open the possibility of a low-mass AGN that does not leave a broad-line imprint on the spectrum or that MACS0417-z5BBG could be a star-forming galaxy in the lull of a bursty star formation history.